Short Circuit Analysis due to Reconfiguration of AC to DC Electric Power System on Tanker Ship with Hybrid Energy Source - Adi Kurniawan; Arialdi Almonda; Sardono Sarwito (Department of Ocean Engineering, 2024)
The conventional AC electric power distribution system on ships has a higher impedance than the DC system, thus providing more significant distribution losses. Due to the enormous losses in the distribution system, a larger power output is required to balance the power required by the loads, and the losses occur on the line between the sources and the loads. Therefore, reconfiguring the power distribution to the DC system is promising. However, analysis in other aspects needs to be performed, including for short circuit current. In this research, power system simulator software is used to analyze the amount of fault current that contributes to each type of distribution. The simulation is performed under four ship operation modes, including sailing, maneuvering, at port, and cargo loading-unloading. The results of the simulation show that the short-circuit current can be significantly decreased after the reconfiguration of the system. A similar phenomenon has occurred in other operation modes. The short circuit value decreases around ten times in the DC system compared to the AC system. Therefore, the DC system is safer than the AC system.